2011
DOI: 10.1177/152692481102100203
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Addressing Barriers to African American and Non—African American Families' Discussions about Preemptive Living Related Kidney Transplantation

Abstract: Families identified several barriers to discussing preemptive LRKT that could be addressed by social workers. Further research must be done to determine whether social workers need to tailor interventions to address families' cultural differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 19 publications
1
53
1
Order By: Relevance
“…A survey conducted in the United States found that public attitudes toward incentives for living kidney donation varied by ethnicity and income levels (38). We did not observe any apparent differences in opinion among the focus group participants by sociodemographic characteristics, including ethnicity, sex, age, or employment status (including poverty or reduced income).…”
Section: Discussioncontrasting
confidence: 63%
“…A survey conducted in the United States found that public attitudes toward incentives for living kidney donation varied by ethnicity and income levels (38). We did not observe any apparent differences in opinion among the focus group participants by sociodemographic characteristics, including ethnicity, sex, age, or employment status (including poverty or reduced income).…”
Section: Discussioncontrasting
confidence: 63%
“…24 Patient-, system-, and donor-related factors may all contribute to the lower likelihood of living donor transplantation in African-American ESRD patients, but available studies have primarily focused on patient-level factors, many of which overlap with determinants of living donor transplantation in lowincome populations. [25][26][27][28][29] More recently, attention has shifted to transplant center-level practices that affect LKD. 22 However, there has been less emphasis on donor-related factors in the published literature, and most of the available studies actually address recipient-related factors contributing to decreased identification of potential living donors in ethnic minority groups.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies indicate that patient concerns and perceived knowledge about end stage dialysis treatment options are determinants of patient behavior (3, 6, 8, 9, 12, 15). Also, patient education has been associated with improved graft and patient survival following transplantation as well as decreased racial disparities in transplantation (16, 17).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of barriers to transplantation have often been focused on racial disparities (11, 12). An expanded assessment of patient-reported thoughts, beliefs and concerns, beyond considerations of racial disparities, is necessary to better understand factors that may contribute to patient’s not completing their evaluation.…”
Section: Introductionmentioning
confidence: 99%